Trypan blue assisted phacoemulsification in corneal opacities. Issue 8 (1st August 2002) - Bhartiya, P; Sharma, N; Ray, M; Sinha, R; Vajpayee, R B
Abstract : Aim: To evaluate the efficacy of trypan blue for enhancing visualisation during phacoemulsification and foldable lens implantation in cases of cataract with corneal opacities. Methods: 11 eyes of 11 patients with nebulomacular corneal opacities involving the visual axis with partially and visually debilitating cataract underwent trypan blue assisted phacoemulsification with foldable intraocular lens implantation. The patients were followed at the first day, first week, first month, and third month postoperatively. Completion of capsulorhexis, phacoemulsification with foldable lens implantation, and postoperative best corrected visual acuity were measured. Results: The dye improved visualisation of the anterior capsule and a complete capsulorhexis could be performed successfully in all eyes. In all but one eye phacoemulsification was accomplished successfully. In one eye with Fuchs' dystrophy penetrating keratoplasty was performed later. Visual acuity was ≤6/60 preoperatively in all eyes and improved to ≥6/24 in eight eyes postoperatively. Conclusion: Trypan blue assisted phacoemulsification may be performed in selected cases of corneal haze/opacification with cataract. It provides acceptable visual outcome in cases awaiting penetrating keratoplasty or in cases where it is not feasible or promising.